Systematic Literature Review: Profesionalisme Guru Dalam Mengintegrasikan Keterampilan Metakognitif Untuk Meningkatkan Kualitas Pembelajaran Sejarah - Razin Faldam; MGS Hasrul Haris; Suhendro Suhendro; Syarifuddin Syarifuddin; Ferralia Eka Putri (Peneliti.net, 2026)
History instruction in schools still tends tofocus on rote memorization, and thus has not been optimal in developing students’higher-order thinking skills. This situation highlights the need to integratemetacognitive skills supported by teacher professionalism. This studyaims to analyze the role of teacher professionalism inintegrating metacognitive skills into history instruction. The methodused was a Systematic Literature Review (SLR) withthe PRISMA approach applied to fourteen relevant articles. The results of the reviewindicate that teacher professionalism plays a significant role in designingstudent-centered learning through the application of strategies such as problembased learning, inquiry learning, and self-regulated learning.The integration of metacognitive skills—including planning, monitoring, andevaluation—has been proven to enhance student engagement, independence, andcritical thinking skills in understanding historical events. However, its implementationstill faces challenges in the form of limited teacher understanding andconventional teaching practices. Therefore, continuous improvement ofteacher professionalism is necessary to ensure that metacognitive integrationcan function optimally.